The first ninety years a Sumerian celebration in honor of Miguel Civil - Feliu, Lluís 1965-; Karahashi, Fumi; Rubio, Gonzalo; Civil, Miguel 1926-2019 (Boston Berlin De Gruyter, 2017)
Frontmatter -- Contents -- Preface -- Bibliography of Miguel Civil5 (1991–2016) -- Tabula Gratulatoria -- “As I write this letter to you”: An Attempt at the Letter from Nanna-manšum to Rīm-Sîn? -- À tâtons dans le noir : À la recherche du sens de ḫabātum -- “Enlil and Namzitara” Reconsidered -- ‘Let me be your canal’: some thoughts on agricultural landscape and female bodies in Sumero-Akkadian sources -- The Eridu Project (AMEr) and a Singular Brick-Inscription of Amar- Suena from Abū Šahrain -- The Silences of the Scribes, Pt. II: An Unfinished Enlil Lament from Nippur -- A New Seal of the Scribe Ur-Nanše from Girsu -- Texts and Workers -- Emesal studies today: a preliminary assessment -- Royal Nurses and Midwives in Presargonic Lagaš Texts -- The Hymn to the Ekur: Its Literary Structure and Cultic Background -- Game of Thrones: the Years when Šu-Sin Succeeded Amar-Suen in the Kingdom of Ur -- Literary Journeys from Babylonia to Assyria: Second Millennium Copies of a Bilingual Poem Concerning Ninurta -- New Data on Garšana and the Border Zone between Umma and Girsu/Lagaš -- A New Silver Balanced Merchant Account from Umma -- A Middle Babylonian Sumerian Fragment of the Adapa Myth from Nippur and an Overview of the Middle Babylonian Sumerian Literary Corpus at Nippur -- Sumerian Temples and Arabian Horses: On Sumerian e2-gal -- To Carry Coals to Newcastle or Observations Concerning Sign Formation as an Early Concept in Mesopotamian “Commentaries” -- Cuneiform Tablets and Other Inscribed Objects from Collections in Jerusalem -- On Images, Visibility, and Agency of Early Mesopotamian Royal Women -- Words and Grammar: Two Old Babylonian Lists -- The Seven Attendants of Hendursaĝa: A study of animal symbolism in Mesopotamian cultures -- The Abacus in Mesopotamia: Considerations from a Comparative Perspective -- Index of texts and compositions discussed -- Index of words and terms discussed -- Index of personal names discussed
This volume is dedicated to Miguel Civil in celebration of his 90th birthday. Civil has been one of the most influential scholars in the field of Sumerian studies over the course of his long career. This anniversary presents a welcome occasion to reflect on some aspects of the field in which he has been such a driving force
In English
Keywords: Sumerians -- Antiquities; Sumerians -- History; Mesopotamien; sumerische Kultur; sumerische Sprache; Mesopotamian Studies; Sumerian civilization; Sumerian language; HISTORY / Middle East / General; Festschrift; Aufsatzsammlung